Children’s Problem Solving Abilities In Pattern Play Material - Asmidar Parapat; Zannatunnisya; Rika Widya; Almanah Rambe (Yayasan Multidimensi Kreatif, 2024)
One of the abilities that must be developed from an early age is problem solving ability. With this ability, children can develop their thinking skills in solving problems. This problem solving ability aims to overcome their problems in overcoming problems in everyday life. Problem solving ability is related to how children think, understand, remember, the ability to solve problems and make decisions. The focus of this study is the analysis of children's problem solving abilities in playing patterns. The purpose of this study is to determine the problem solving abilities of early childhood. The research design used in this study is a qualitative research design with a case study method. Data collection techniques use observation and interviews. Data analysis techniques use thematic design analysis of data collection, data selection, presenting, and drawing conclusions. The results of the study show problem solving abilities in early childhood through playing patterns, namely playing color patterns, children are able to observe, experiment, compare, and communicate to teachers and peers when a problem occurs while playing.